Antenatal magnesium sulphate for the prevention of cerebral palsy in infants born preterm: a double‐blind, randomised, placebo‐controlled, multi‐centre trial. (29th April 2020) - Wolf, HT; Brok, J; Henriksen, TB; Greisen, G; Salvig, JD; Pryds, O; Hedegaard, M; Weber, T; Hegaard, HK; Pinborg, A; Huusom, LD; ,
Abstract : Objective: To study the effect of antenatal magnesium sulphate (MgSO4 ) on cerebral palsy (CP) in a manner that also provides adequate power for a linked trial sequential analysis. Design: Double‐blind, randomised, placebo‐controlled, multi‐centre trial. Setting: Fourteen Danish obstetric departments. Population: In total, 560 pregnant women at risk for preterm delivery before 32 weeks of gestation were randomised from December 2011 to January 2018. Those women gave birth to 680 children. Methods: Women were randomised to receive either a loading dose of 5 g MgSO4 followed by 1 g/hour or a placebo in identical volumes. The children were followed up at a corrected age of 18 months or older with a review of their medical charts and with the Ages and Stages Questionnaire. Main outcome measure: The primary outcome measure was moderate to severe CP. Secondary outcomes included mortality, neonatal morbidity, blindness and mild CP. Results: The crude rates of moderate to severe CP in the MgSO4 group and the placebo group were 2.0% and 3.3%, respectively. The adjusted odds of moderate to severe CP were lower in the MgSO4 group than in the placebo group (odds ratio 0.61; 95% CI 0.23–1.65). Conclusions: Antenatal MgSO4 before 32 weeks of gestation decreases the likelihood of moderate to severe CP; these results are entirely consistent with other randomised evidence summarised in the linked trial sequential analysis. Tweetable abstract: Antenatal magnesium sulphate may decrease the risk of moderate to severe cerebral palsy in children born before 32 weeks of gestation. Tweetable abstract: Antenatal magnesium sulphate may decrease the risk of moderate to severe cerebral palsy in children born before 32 weeks of gestation.